PENGARUH CORPORATE GOVERNANCE TERHADAP PERINGKAT OBLIGASI DAN YIELD OBLIGASI - Rita, Maria Rio; Sarquella, Lluis (Jurnal Manajemen dan Keuangan, 2010)
This paper investigated the effect of corporate governance to bond rating and bond yield. The proxies of corporate governance are institution ownership, independent committee, and managerial ownership. Those proxies are independent variables, and the dependent variables are bond rating and bond yield.Logistic regression (logit) is used to examine first hypothesis, and multiple regression is used to examine second hypothesis. Sample are all bonds that issued period 2004-2007, and data are collected from Indonesia Stock Exchange and Bisnis Indonesia Daily.The result proved that implementation corporate governance influences bond rating. The existence of independent committee have positive effect to bond rating but the opposite effect is to bond yield. The better of corporate governance implementation the higher bond ratings but bond yields wil decrease.Keyword : Corporate governance, bond rating, and bond yield